2009
DOI: 10.1148/radiol.2501080295
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Transarterial Chemoembolization in the Treatment of Liver Metastases of Colorectal Cancer: Prospective Study

Abstract: Chemoembolization is a minimally invasive therapy option for palliative treatment of liver metastases in patients with colorectal cancer, with similar results among three chemoembolization protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(67 citation statements)
references
References 33 publications
1
65
0
1
Order By: Relevance
“…Most common effects of post-embolization syndrome are pain, nausea, vomiting and fatigue. 7,10 Post-embolization pain represents one of the most common side effects of chemoembolization. Intra-arterial injection of lidocaine has been reported to reduce the severity and duration of postembolization pain.…”
Section: Current Trends In Interventional Treatment Of Colorectal Canmentioning
confidence: 99%
See 2 more Smart Citations
“…Most common effects of post-embolization syndrome are pain, nausea, vomiting and fatigue. 7,10 Post-embolization pain represents one of the most common side effects of chemoembolization. Intra-arterial injection of lidocaine has been reported to reduce the severity and duration of postembolization pain.…”
Section: Current Trends In Interventional Treatment Of Colorectal Canmentioning
confidence: 99%
“…7,10 Several previous studies addressed the safety of performing TACE on an outpatient basis. Mitchell et al 20 reported the safety of the outpatient concept in carefully selected patients, where 131 from 133 sessions were performed on outpatient cases and only 2 required readmission.…”
Section: Current Trends In Interventional Treatment Of Colorectal Canmentioning
confidence: 99%
See 1 more Smart Citation
“…Such treatment methods include hepatic arterial infusion (HAI) of chemotherapy, transarterial chemoembolization (TACE), chemoembolization with chemotherapeutically loaded beads, radiofrequency ablation (RFA), cryotherapy, laser-induced thermotherapy (LITT) and selective internal radiation therapy (SIRT). [22][23][24][25][26][27][28][29][30] Regarding liver metastases of CRC there are few studies addressing the possible prognostic factors of liver metastases from CRC under TACE. The current single-center study was performed on a large number of patients (n 5 564) to determine the response and survival rates of patients who undergo TACE of liver metastases of CRC and to compare the effect of four different regimens of chemotherapy.…”
mentioning
confidence: 99%
“…Several studies suggest that conventional tace is associated with improved survival in patients with chemorefractory crc with liver metastases 66,67 ; however, most studies lack a control group. Phase ii/iii trials using deb-tace have reported response rates of approximately 70%, with pfs durations of 7-8 months and a mos of 22-25 months [68][69][70] .…”
Section: Summary Of Evidencementioning
confidence: 99%